Family ownership and effects on firm performance in Asia - Andreas Hˆgberg (European Regional Science Association (ERSA), 2010)
The current literature on firm ownership around the world shows that concentrated ownership with only one or a few controlling owners is common, especially in many European and Asian countries. The dispersed ownership has proven to be uncommon and even countries with supposed dispersed ownership has also shown signs of ownership concentration. Commonly, the controlling ownership is held by an individual, or a group of individuals, usually with family ties. Family ownership is the most common type of concentrated owner around the world, with pyramidal ownership structures of firms and state ownership are prevalent features of ownership concentration often observed also. The effects on the governance of the firm, the relation between shareholders and management and furthermore the level of investment performance of the firm is all ultimately affecting the economic development around the world. While most previous studies within the ownership literature has been done on publicly traded firms, this paper, however, studies the effect of ownership type and control on firm performance and governance in a large sample of both public and private European and Asian firms.
Keywords: G30; G32; L25; 330; Corporate governance; firm performance; ownership